On the Efficacy of a Platform in a Semi-pelagic Trawl - T., Joseph Mathai; M., Syed Abbas; R.S., Manoharadoss; V., Vijayan (Fishery Technology, 2025)
Fishing performance of a 20m semi-pelagic trawl additionally equipped with a platform panel as a forward extension of lower belly, has been evaluated in this paper, based on comparative field trials with a control gear, from a 10.9m LOA wooden trawler (65 hp) in the waters off Mormugao. Significant improvement in the catch of quality fishes by 68.4% (p<0.05), other fish categories by 92.2% (p<0.01) and total landings by 86% (p<0.001) has been obtained with the experimental gear with platform panel, compared to the control gear. Improved performance of the experimental gear is attributed to the effective prevention of downward escapement of fishes by the platform panel, during the fish capture process.